Pengaruh Sistem Informasi Akuntansi, Partisipasi Penyusunan Anggaran dan Pengendalian Internal Terhadap Kinerja Manajerial pada Perumda Air Minum Tirta Tamiang Kabupaten Aceh Tamiang - Muzdalifa, Yayang; Dalimunthe, Hasbiana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research aims to determine the influence of accounting information systems, budget preparation participation, and internal control on managerial performance at Perumda Air Minum Tirta Tamiang, Aceh Tamiang Regency. The type of research carried out is causal associative research. This research was conducted on company employees using a purposive sampling technique, with a total sample of 35 people. The data collection technique was obtained through a questionnaire which was measured using a Likert scale and statistically processed with the help of SPSS version 27.00 For Windows. Data analysis techniques use descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression analysis, hypothesis tests and coefficient of determination tests. The research results show that partially the accounting information system, participation in budget preparation, and internal control have a positive and significant effect on managerial performance. Simultaneously accounting information systems, participation in budgeting and internal control have a positive and significant effect on managerial performance.